Implementation of Anti-Corruption Ethics in the Field of Education - Situmorang, Marlinawati (the International Journal of Education, Theology, and Humanities, 2023)
Efforts to deal with corruption crimes committed by the government against corruptors have been going well but have not produced optimal results as expected. The complexity of the corruption problem in Indonesia is not sufficient to overcome by relying solely on preventive and investigative strategies, but an educative strategy is also needed. The eradication of corruption requires multi-disciplinary, strategic, comprehensive, and simultaneous efforts. Therefore, one of the possible efforts to prevent corruption is to involve the formal education sector. This is the aim of this research. However, there is a challenge that so far, the national education system has been poisoned by elements of Collusion, Corruption and Nepotism (KKN). As a closed system, it is very easy for material and non-material corruption practices to occur. KKN practices that also occur in the body of the national education system, by itself has degraded the quality and lofty ideals of education, because the limited sources of funds are not enjoyed by many people. Using a qualitative method through a literature research approach, researchers observed that corruption prevention in formal education institutions can be done through two approaches. First, making students as the target in the form of improving the morals and personality of students, so as not only to produce humans who are intellectually intelligent, but also morally good. Second, using students to suppress the environment so that it is not permissive and easy to commit corruption, by providing enrichment materials that can encourage students to become perpetrators of corruption prevention.